Preclinical study and parallel phase II trial evaluating antisense STAT3 oligonucleotide and checkpoint blockade for advanced pancreatic, non-small cell lung cancer and mismatch repair-deficient colorectal cancer - Heather Lin; Vivek Subbiah; Siqing Fu; Aung Naing; Courtney Nicholas; Shubham Pant; Chad Tang; Michael A Curran; David S Hong; Ying Yuan; Sarina A Piha-Paul; Jordi Rodon Ahnert; et al. (BMJ Oncology)
Objective To evaluate signal transducer and activator of transcription 3 (STAT3) inhibition we conducted a co-clinical trial testing danvatirsen, a STAT3 antisense oligonucleotide (ASO) and checkpoint inhibition in conjunction with preclinical experiments.Methods and analysis Orthotopically implanted pancreatic cancer (pancreatic adenocarcinoma (PDAC)) was treated with STAT3 ASO with immune checkpoint inhibition. Tumour infiltrating immune cell populations were characterised via flow cytometry. In vitro experiments evaluated STAT3 inhibition in pancreatic stellate cells (PSCs) and myeloid-derived suppressor cells (MDSCs).A phase II trial employing a Simon II stage design tested the clinical efficacy of danvatirsen and durvalumab in non-small cell lung cancer (NSCLC), PDAC and mismatch repair-deficient colorectal cancer (MRD CRC). The primary objective was 4-month disease control rate (DCR).Results In vivo studies identified improvement in survival of PDAC implanted mice treated with STAT3 ASO and checkpoint inhibition. Within tumour-infiltrating lymphocytes there was expansion of CD4 and PD-1+ CD8 populations with STAT3 ASO.Thirty-seven patients (29 PDAC, 7 NSCLC and 1 MRD CRC) from a single institution started treatment on trial between April 2017 and March 2020. No objective responses were observed. Four of six (66.7%, 95% CI 22.3% to 95.7%) NSCLC and 4 of 23 (17.4%, 95% CI 5% to 38.8%) PDAC patients exhibited 4-month DCR. Follow-up in vitro studies revealed an anti-inflammatory and pro-tumour effect of STAT3 ASO mediated by PSCs and MDSCs distinct from ablation of STAT3.Conclusion Although durvalumab and danvatirsen met the primary endpoint, no objective responses were observed. A rationale for the lack of objective responses is danvatirsen-induced myeloid immune suppression.Trial registration number NCT02983578.